The future of work: How G20 countries can leverage digital-industrial innovations into stronger high-quality jobs growth - Marco Annunziata; Hendrik Bourgeois (Kiel Institute for the World Economy (IfW), 2018)
A new wave of innovation is beginning to disrupt industry on a global scale. It constitutes a tremendous opportunity for faster productivity growth, but also a potential disruption to a number of economic sectors and to job markets. Academic research and the public debate have focused mostly on the threat that innovation poses to jobs and wages. This paper instead suggests that (i) these same technological disruptions make human capital more important than ever for companies' strategies; (ii) greater attention needs to be devoted to new forms of complementarity between new technologies and human capital. While some jobs will be displaced, the greatest impact of innovation will come in the way that many jobs will be transformed; the evidence to date supports the authors' view that innovation will once again result in more and better jobs - but much work needs to be done to optimize the transition. In particular, more effort should be devoted to (i) understanding what new skills will be needed, and how existing jobs will change; (ii) upgrading education and professional training schemes; (iii) reforming labor market institutions to support a future where a larger share of workers will change jobs and employers more frequently, and more people will work independently in a crowdsourcing or "gig economy" framework; (iv) reforming social benefits systems and bolstering social safety nets to smooth the economic transition and cushion the impact on the worst-affected workers. As innovation disrupts a growing number of industries, human capital strategies will need the collaboration of companies, educational institutions, governments and multilateral policy agencies. This paper presents an analysis of the challenges, addresses the key areas of action, and puts forward some specific proposals, including policy actions, industry initiatives, and further research projects. The authors argue that the G20 could and should champion a comprehensive approach to leverage digital-industrial innovations for faster job creation and growth, with measures to re-align demand and supply of skills, labor market reforms, redesigned social safety nets, measures to promote digital innovation and facilitate the adoption of skills-augmenting technologies. Private sector companies should strengthen training programs. International cooperation, standards harmonization and interoperability will be essential to maximize the benefits and minimize the disruptions - the G20 can therefore play a key role.
Keywords: J20; J23; J24; J62; J68; O32; O33; M5; I28; E24; D24; 330; innovation; productivity; technological unemployment; training; education; manufacturing; R&D; investment